The Influence of Store Atmosphere, Price Discount, and Service Quality on Consumer Satisfaction at Sociolla Store Pakuwon Mall Surabaya - Cyntia Ayu Sukmaningati; Lia Nirawati (Universitas KH. Abdul Chalim Mojokerto, 2026)
Indonesia's dynamic retail sector, particularly its burgeoning beauty industry, increasingly demands experience-centric strategies to sustain competitiveness amidst rapid technological shifts and evolving consumer demands. Sociolla Store Pakuwon Mall Surabaya, a prominent player, nonetheless navigates persistent operational challenges, including pricing inconsistencies and fluctuating service quality during peak promotional periods, underscoring the critical need to optimize its in-store dynamics. This quantitative associative causal study meticulously analyzes the impact of store atmosphere, price discount, and service quality on consumer satisfaction. Data collected from 155 purposively sampled Sociolla consumers via online questionnaires ensured robust reliability through Cochran's formula. Analysis using SPSS 27 included classical assumption testing and multiple linear regression. Findings conclusively reveal all three variables simultaneously and significantly influence consumer satisfaction (based on the uji F, with a significance level of less than 0.001). Individually, a well-crafted store atmosphere (based on the uji t, also significant at p < 0.001) and high service quality (based on the uji t, significant at p < 0.001) demonstrably enhance satisfaction. Notably, price discount (based on the uji t, with p = 0.587) surprisingly exhibits no significant partial influence, underscoring consumers' distinct prioritization of holistic experiential factors over purely financial incentives in this specific retail context. This research enriches marketing theory by highlighting the dominance of experiential value, simultaneously guiding retailers to prioritize ambiance and service excellence for fostering long-term customer loyalty.